Time to Step Up: A Call to Action For the Clinical and Quantitative Pharmacology Community to Accelerate Therapeutics for COVID‐19 - Hartman, Dan (Clin Transl Sci, 2020)
The global response to finding therapeutics for coronavirus disease 2019 (COVID‐19) is chaotic even if well intentioned. There is an opportunity, but more importantly, an obligation for the global clinical and quantitative pharmacology community to come together and use our state‐of‐the‐art tools and expertise to help society accelerate therapeutics to fight COVID‐19. This brief commentary is a call to action and highlights how the global pharmacology community should contribute to the COVID‐19 pandemic and prepare for future pandemics.